The effectiveness of a proposed strategy in light of anchored instruetion learning on achievement among middle school students - Hassoon Suhail, AYSAR; Jabbar Faris, Elham (Edelweiss Applied Science and Technology, 2024)
The research aims to identify the effectiveness of a proposed strategy in light of Anchored instruetion Learning in achieving achievement among middle school students. To achieve the aim of the research, the two researchers adopted an experimental research approach with two groups (experimental and control) with a post-test, and the null hypothesis was developed: There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who studied according to the proposed strategy and the scores of the control group students who studied according to the normal method in the achievement test. The research sample consisted of (60) fifth-grade science students at Al-Suyuti Preparatory School affiliated with the General Directorate of Education of Baghdad Al-Karkh II. The sample was distributed into two groups: The experimental group consisted of (30) students who studied according to the proposed strategy. 2. The control group consisted of (30) students who studied in the usual way. The two research groups were rewarded on the variables (previous achievement, chronological age, previous knowledge, intelligence, and mathematical culture). After that, an achievement test was constructed, consisting of (30) objective, multiple-choice items. Appropriate statistical analyzes were conducted, and the psychometric properties of the test were verified. The results resulted The students in the experimental group who studied with the proposed strategy outperformed the students in the control group who studied in the usual way. In light of the results, a set of conclusions, recommendations and proposals were reached.